The Molecular Biology of Brain Metastasis. (8th March 2012) - Rahmathulla, Gazanfar; Toms, Steven A.; Weil, Robert J.
Abstract : Metastasis to the central nervous system (CNS) remains a major cause of morbidity and mortality in patients with systemic cancers. Various crucial interactions between the brain environment and tumor cells take place during the development of the cancer at its new location. The rapid expansion in molecular biology and genetics has advanced our knowledge of the underlying mechanisms involved, from invasion to final colonization of new organ tissues. Understanding the various events occurring at each stage should enable targeted drug delivery and individualized treatments for patients, with better outcomes and fewer side effects. This paper summarizes the principal molecular and genetic mechanisms that underlie the development of brain metastasis (BrM).